DETERMINAN KINERJA PEGAWAI PEMERINTAH KOTA LANGSA (STUDI PADA OPD KOTA LANGSA) - Azhar, Iqlima; Afrah Junita; Novia Veronika (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the effect of HR competency, SAP implementation and role ambiguity simultaneously on employee performance in OPD of Langsa City. The sample used in this study were the Secretary, Head of General Affairs and Head of Personnel in 34 OPDs of Langsa City. The determination of the sample was because each employee will be responsible for the results of their work to the Head of Service either directly or through the secretary. Based on respondent data from 34 OPDs of Langsa City and each OPD was taken 3 respondents, the number of samples in this study was 102 respondents. The data analysis method used multiple linear regression analysis, t-test, F-test and determination coefficient test. The regression equation in this study is Y = 5.290 + 0.147X1 + 0.363X2 + 0.275X3. Human resource competency has a significant effect on employee performance in OPD of Langsa City. SAP implementation has a significant effect on employee performance in OPD of Langsa City. Role ambiguity has a significant effect on employee performance in OPD of Langsa City. Role ambiguity, SAP implementation and role ambiguity simultaneously have a significant effect on employee performance at OPD of Langsa City. From the determination coefficient test, it is known that human resource competence, SAP implementation and role ambiguity affect employee performance at OPD of Langsa City by 63.1%, while the remaining 36.9% is influenced by other variables outside this research model. This research was conducted with limitations, so the results can change due to these limitations. This study had difficulty obtaining the data or respondents needed for the study. This study was also unable to fully control the honesty and sincerity of respondents in choosing answer options that were in accordance with the actual circumstances and reality. For further researchers, it is better to conduct a study by deepening the scope of the study by adding variables or replacing other variables.